Risk assessment of attitudes and practices of students and practitioners toward studio dyeing in Ghana. (9th September 2019) - Howard, Ebenezer Kofi; Frimpong, Charles; Seidu, Raphael Kanyire
Abstract : Purpose: The purpose of this study is to assess the attitudes and practices of students and practitioners in the dyeing studio. Empirical evidence shows that synthetic dyes are the most commonly used dyestuff because of their colour fastness as compared with natural dyes. However, it is proven scientifically that synthetic dyes and their auxiliaries are carcinogenic and allergenic, which pose as health risks to users. Design/methodology/approach: The study used analytical observational study design, where observation, questionnaire and interview were the instruments for data collection. Findings: A survey conducted at selected dyeing studios in Ghana revealed the excessive use of vat dyes by students and practitioners because of its availability and accessibility on the local market. Adversely, the study found non-use of personal protective equipment by students and practitioners for protection against hazardous effects of dye chemicals. Again, poor studio set up with limited space and lack of proper waste drainage systems at the various dyeing studios results in inappropriate disposal of dyes, leading to environmental pollution. Originality/value: Dyeing throughout history has been practiced to colour a fabric or yarn for specific use in the environment, which brings in some revenue. This practice however employs the use of dyes coupled with its auxiliaries, which poses some health problems in the short, medium and long term because of certain attitudes and practices exhibited by students and practitioners in the studio. It is therefore imperative for effective compliance to safety rules and practices by students and practitioners to ensure their safety. It is also critical that educational institutions and practitioners build modern dyeing studios which are spacious, well ventilated and efficient in limiting environmental pollution in compliance with eco-friendly practices. The study further recommends collaboration between Academia, local dyers' association, Ghana Health Service and the Environmental Protection Agency to organize workshops to ensure best safety practices to save lives and the environment.